Saliva and GCF cytokine levels in insulin-dependent diabetic teens and their relationship with metabolic status and disease duration - Akkemik, Ozlem; Kesim, Servet; Renklibay, Ela Cabuk; Okdemir, Deniz; Saraymen, Recep; Kurtoglu, Selim (Elsevier, 2023)
Objective: Hyperglycemia damages periodontal tissues by several mechanisms, primarily via dysregulated cytokine production. However, studies examining the relationship between cytokine levels, periodontal status, and diabetes-related parameters in teenage Type 1 Diabetes Mellitus (T1DM) patients are scarce. This investigation aimed to determine the levels of cytokines such as IL-33, IL-22, IL-17, IL-6, TNF-a and interferon (IFN)-g in the saliva and gingival crevicular fluid (GCF) of T1DM teens and correlate these values with the patients' periodontal health and DM-related parameters such as FBG, HbA1c, and diabetes duration.Material and methods: Saliva, GCF samples and full-mouth clinical periodontal recordings were obtained from 40 T1DM and 40 non-diabetic teenagers. IFN-g, TNF-a, IL-6, IL-17, IL-22, and IL-33 levels were analyzed by ELISA.Results: Clinical bleeding on probing (BOP) and periodontal probing depth measures did not differ between the groups. The plaque and gingival index, as well as saliva and GCF levels of all cytokines tested were found to be comparatively higher in the cases. Correlations were detected between the duration of DM and salivary IL-17 and IL-33 levels, between FBG and GCF IL-17 levels, and between BOP and salivary IL-33 levels. Salivary IL-17 and IL-33 levels showed significant correlation solely with the duration of DM.Conclusions: IL-33 and IL-17 appear to be a potent combination of cytokines in regulating salivary composition over time in Type I diabetic teens. A better understanding of the time-dependent release of salivary cytokines in Type I diabetic teens may help develop treatment strategies and improve oral health.(c) 2023 Published by Elsevier Ltd on behalf of Japanese Society of Pediatric Dentistry.
Keywords: Type I diabetes; Periodontal health; Cytokines; Saliva; Gingival crevicular fluid